Gnomeo & Juliet [videorecording (DVD)] - Asbury, Kelly; Blunt, Emily; McAvoy, James, 1979-; Statham, Jason, 1967-; Smith, Maggie, 1934-; Caine, Michael; Stewart, Patrick, 1940-; Osbourne, Ozzy, 1948-; John, Elton (Buena Vista Home Entertainment, 2011)
Caught up in a feud between neighbors, Gnomeo and Juliet must overcome as many obstacles as their namesakes. But with flamboyant pink flamingoes and epic lawnmower races, can this young couple find lasting happiness?